Results of Trifocal Intraocular Lenses Implantation in Patients with Cataract and Presbyopia - E. I. Belikova; V. A. Borzykh (Oftalʹmologiâ)
Purpose: to evaluate the clinical results of trifocal intraocular lenses implantation with different optical characteristics; optimization of preparation stages and intraocular correction of presbyopia. Patients and Methods. Phacoemulsification with binocular implantation of trifocal intraocular lenses (IOL) was performed in 35 patients with cataract and presbyopia. IOL AcrySof® IQ PanOptix® was implanted in 32 eyes, AT LISAtri839MP — 38 eyes. Preoperative evaluation included standard examination with surgeon’s consultation and clarification of patients’ lifestyle and vision motivations at all distances. Postoperative evaluation included measurement of refraction, visual acuity at three distances, quality and visual acuity under mesopic conditions. Proposed to use the test questionnaire, visual acuity testing tables at intermediate distances, nomograms for IOLs power calculation developed by the authors. Results. Postoperative spherical refraction was 0.17 ± 0.23D, which did not exceed 0.5D deviation from the target refraction. Uncorrected distance visual acuity ≤ 0.5 reached in 100 % of patients on the first day after surgery. Visual acuity ≤ 0.5 at intermediate distance was achieved in 34 eyes (89.5 %) of patients with implanted IOL AT LISAtri, and the same results has been recorded for near in 33 eyes (86.8 %). On the next day after surgery in the PanOptix® group, all patients monocular gave ≤ 0.6 for intermediate and near, and 96.9 % of eyes ≤ 0.5 for far. All patients from both groups (PanOptix® or LISAtri) after 6 months binocular showed visual acuity ≤ 0.8 for far, near or intermediate distances, no patient noted a need to use any spectacle correction and did not notice significant visual impairment in mesopic conditions. Conclusion. Implantation of Trifocal IOLs AcrySof® IQ PanOptix® and AT LISAtri 839MP allows patients spectacle independence and high-quality of vision in mesopic conditions. An individual approach to each patient, concomitant ophthalmopathology, general status, life style, primary refraction and precise IOLs power calculation, allows the surgeon widely to apply this technology for presbyopia intraocular correction.